2010
DOI: 10.1111/j.1469-8749.2009.03415.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies in children with cerebral palsy: a population‐based record linkage study

Abstract: AIM Our aim was to determine the proportion of children with cerebral palsy (CP) who have a congenital anomaly (CA) in three regions (Isè re Region, French Alps; Funen County, Denmark; Northern Region, England) where population-based CP and CA registries exist, and to classify the children according to CA subtype.METHOD Data for children born between 1991 and 1999 were linked using electronic matching of cases. All potential matches were checked manually by each centre and verified as true matches.RESULTS A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
99
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 28 publications
15
99
3
1
Order By: Relevance
“…It is, therefore, the more convincing that the same conclusions have been reached by Rankin et al 4 This work has taken further the investigation reported by Garne and European collaborators in 2008. 5 This simply compared the prevalence of congenital malformations reported in a number of high quality and standardized CP registers with that estimated using local population-based congenital malformation registers.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…It is, therefore, the more convincing that the same conclusions have been reached by Rankin et al 4 This work has taken further the investigation reported by Garne and European collaborators in 2008. 5 This simply compared the prevalence of congenital malformations reported in a number of high quality and standardized CP registers with that estimated using local population-based congenital malformation registers.…”
supporting
confidence: 83%
“…5 This simply compared the prevalence of congenital malformations reported in a number of high quality and standardized CP registers with that estimated using local population-based congenital malformation registers. Rankin et al 4 linked cases in three CP registers with those in local congenital malformation registers, thus obtaining more clinical information on the matched children. As in the much earlier literature, the excess of congenital malformations in the cerebral palsies was found particularly in children with spastic types of CP rather than dystonia or athetosis, and in those who were term births.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] A study based on the CP Register and the Birth Defect Registry of Western Australia reported that 15.8% of children with CP had non-CNS anomalies. 19 Pharaoh 21 demonstrated an increase in eye anomalies, cardiac anomalies, cleft lip and ⁄ or palate, congenital dislocation of the hip and talipes, and atresias of the oesophagus and intestines in children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] It has been documented that CP occurs in 2-2.5/1 000 live births. 10 Causes of CP include being born before term, not receiving enough oxygen during the birth, the foetus being exposed to maternal infection and/or inflammation in utero, and maternal fever during labour.…”
Section: Cerebral Palsymentioning
confidence: 99%